The Relationship Between the Use of Peppermint Aromatherapy in Reducing Hyperemesis During Pregnancy at Poleang Timur Public Health Center, Bombana Regency, Southeast Sulawesi - Alvionita, Vinny; Khair, Ummul; Andi Kaso, Iin Ilma (Papua Medicine and Health Science, 2024)
Hyperemesis gravidarum (HG) is one of the most common complaints during pregnancy, affecting approximately 70-80% of all pregnant women with symptoms of morning sickness. Around 60% of pregnant women also experience vomiting. If not properly managed, persistent nausea and vomiting can develop into severe hyperemesis gravidarum. Hyperemesis gravidarum can have adverse effects on the health of both the mother and fetus, including slowing blood circulation, reducing oxygen and nutrient supply to tissues, and potentially causing tissue damage that endangers maternal and fetal health. Objective: To determine the relationship between the use of peppermint aromatherapy in reducing hyperemesis during pregnancy at Poleang Timur Public Health Center in 2024. Method: This study used an analytical survey with a cross-sectional approach. The population in this study consisted of all pregnant women experiencing hyperemesis, with a total sample of 51 respondents obtained through total sampling. Data collection was conducted using an observation sheet with a checklist. The data were processed using SPSS 20 and analyzed with the Chi-Square Test. Results: The analysis of peppermint aromatherapy usage showed a p-value of 0.007 < 0.05, leading to the conclusion that the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. Conclusion: There is a significant relationship between the use of peppermint aromatherapy and the reduction of hyperemesis during pregnancy at Poleang Timur Public Health Center in 2024.